Hubungan Karakteristik Ibu Dengan Kejadian Anemia Pada Ibu Hamil Di Puskesmas Ikua Koto Tahun 2023 - Afrah Diba Faisal; Epi Satria; Novi Maya Sari (KOLONI, 2023)
In Indonesia, the prevalence of anemia in pregnancy is still high, which is around 89.6% of the total number of pregnancies of 1.5 million pregnant women. This can be one of the causes of the high maternal mortality rate (MMR) in Indonesia. Characteristics of mothers with anemia incidence in pregnant women in the Ikua Koto health center area in the city of Padang in 2023. The type of research is analytic which was carried out at the Ikua Koto Health Center in Padang City from April 1 to 30 2023 with a total of 70 respondents. Sampling was carried out by accidental sampling technique using a questionnaire as a research instrument, the data was processed univariately and bivariately with the Chi squere test. From the results of the study, it was found that there was no significant relationship between education level and the incidence of anemia in pregnant women. (p-value 0.0.33), there is no significant relationship between maternal employment status and the incidence of anemia in pregnant women (p-value 0.183), there is no significant relationship between maternal parity and the incidence of anemia in pregnant women. (p-value 0.329), there is no significant relationship between the level of knowledge of the mother and the incidence of anemia in pregnant women (p-value 0.386). It is hoped that health workers, especially health workers, in carrying out health promotion for pregnant women will place more emphasis on the changes that occur in pregnant women, especially the promotion of anemia in pregnant women. Keywords: characteristics, anemia, pregnant women